Piezoelectric energy harvester for wind turbine blades based on bistable response of a composite beam in post-buckling - Plagianakos, Theofanis S; Leventakis, Nikolaos; Chrysochoidis, Nikolaos A; Kardarakos, Grigorios-Christos; Margelis, Nikolaos; Bolanakis, Georgios; Papadopoulos, Evangelos G; Saravanos, Dimitris A (Smart materials and structures, 2024)
A bistable piezoelectric energy harvester (PEH) is presented for harvesting power from vibrations occurring at low frequencies, as is the case of wind turbine blades. The axial compressive prestress of a piezoelectric composite beam at post-buckling serves as the bistability source, leading to high mechanical to electric power conversion. An in-house harvesting circuit connected to the piezoelectric terminals is used for demonstration of its harvesting power capabilities. A finite element (FE) model is used to analyze and optimize the coupled nonlinear electromechanical response of the PEH, including structure and circuit. A physical prototype has been manufactured and tested for validation of the electromechanical design and the FE modeling approach. Predictions and measurements indicate an increase of harvested power with applied prestress up to a transition point, where a sudden drop in power occurs. Good comparison between numerical and experimental results verified the modeling approach, whereas deviations related to physical boundary conditions at large compressive forces affected the prediction of the transition point in harvested power. The harvester produced 1.32 mW of electrical power under tonal base excitation of 1 g at 8 Hz. Hence, the nonlinear PEH has demonstrated its capability to harvest energy at frequencies much lower than its first linear modal frequency and could thus serve as a promising solution for powering IoT devices and sensors in large vibrating structures.